Shanaya Tea Si Teh Unik Salah Satu Sektor Industri Ekonomi Kreatif Pematangsiantar - Jhoni F. Manurung; Annisa F. Anggreini; Dian G. Purba; Yessy Febriyani; Fadly A. Lein; Nadilla S. Girsang; Sifa A. S. Guechi; Fadillah R. M. Siregar (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2023)
Tea has become a very popular beverage around the world due to its diverse flavors and rich health benefits. There are many types of tea, including green, black, white, long tea and each of these teas has unique characteristics in its processing and antioxidant content. The purpose of this research was made, to observe and see the uniqueness of Shanaya Tea because it has a unique tea flavor that not many people know, and to help raise the name Shanaya Tea so that it is always remembered by the community, that in Pematangsiantar City if you don't buy tea from Shanya Tea it's not steady. Our group collects data through direct interviews with the owner as the owner of Shanaya Tea. The result of this scientific work is to see that there are still many creative economy industry sectors around Pematangsiantar City that we should be proud of and make souvenirs for future migrants.